MOS device reliability studies under LabVIEW environment - Paulsen, Ron (1994 International Electron Devices Meeting, 1994)
The suitability of the LabVIEW system for a device research laboratory is evaluated. The system is applied successfully to the study of MOS device reliability with the highly repetitive measurement technique of charge pumping. Interface and near-interface oxide trap generation due to hot electron injection from a vertical field injection structure is characterized with the developed software. >